2013
DOI: 10.2478/s11535-013-0137-x
|View full text |Cite
|
Sign up to set email alerts
|

Adult stem cells derived from skeletal muscle — biology and potential

Abstract: Skeletal muscle contains at least two distinct populations of adult stem cells — satellite cells and multipotent muscle-derived stem cells. Monopotential satellite cells are located under the basal lamina of muscle fibers. They are capable of giving rise only to cells of myogenic lineage, which play an important role in the processes of muscle regeneration. Multipotent muscle-derived stem cells are considered to be predecessors of the satellite cells. Under proper conditions, both in vitro and in vivo, they un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Skeletal muscle can regenerate new muscle fibers, when it has been injured or as a consequence of diseases . Muscle regeneration mainly depends on satellite/stem/progenitor cells, which localized between the basal lamina and the muscle fiber membrane . Several animal studies and clinical trials have been reported to investigate the therapeutic potential of intramuscular injection of normal skeletal myoblasts on Duchenne muscular dystrophy; however, there were some problems to affect the results, including the low survival and migration of donor cells and rejection of the donor cells .…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle can regenerate new muscle fibers, when it has been injured or as a consequence of diseases . Muscle regeneration mainly depends on satellite/stem/progenitor cells, which localized between the basal lamina and the muscle fiber membrane . Several animal studies and clinical trials have been reported to investigate the therapeutic potential of intramuscular injection of normal skeletal myoblasts on Duchenne muscular dystrophy; however, there were some problems to affect the results, including the low survival and migration of donor cells and rejection of the donor cells .…”
Section: Discussionmentioning
confidence: 99%